Chemical reactions of tetrahydrofuran and cyclopentane hydrate by dielectric barrier discharge irradiation. (17th July 2020) - Mukasa, Shinobu; Tokuda, Jumpei; Higashise, Taiki; Yamamoto, Shunya; Nomura, Shinfuku
Abstract: We propose clathrate hydrate as a unique chemical reaction field because of its crystalline structure and high density of guest molecules. The products from tetrahydrofuran (THF) and cyclopentane (CP) hydrates by dielectric barrier discharge (DBD) irradiation were investigated at atmospheric pressure. The products were compared to those obtained by DBD irradiation of THF aqueous solution and CP/water-phase liquid. Fewer THF dimers were formed by irradiation of THF hydrates than by the irradiation of the THF aqueous solution. By introducing methane to THF hydrate, the formation of THF dimers was increased. Meanwhile, CP dimers were formed specifically by the irradiation of CP hydrates and were almost never formed by the irradiation of the CP/water-phase liquid. The difference between THF and CP in dimer formation is due to water solubility. The generation of carboxylic acid was suppressed by the irradiation of CP hydrates more than by the irradiation of the CP/water-phase liquid.